2016
DOI: 10.1186/s12909-016-0608-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the first open-access hepatitis B and safe injection online training course for health professionals in China

Abstract: BackgroundDespite the high prevalence of chronic hepatitis B virus (HBV) infection in China, HBV infection prevention and long-term care knowledge of health professionals is inadequate. To address this knowledge gap, we developed an open-access evidence-based online training course, "KnowHBV", to train health professionals on prevention of HBV transmission and safe injections. We conducted an evaluation of the course with health professionals in China to examine its effectiveness in improving knowledge and lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
1
10
0
3
Order By: Relevance
“…The questionnaire was developed in Vietnamese based on the Asian Liver Center at Stanford University’s prior experiences in HBV knowledge surveys in HCWs [1315]. The questionnaire was pre-tested on seven volunteer HCWs to test the questions’ language, flow and comprehension.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire was developed in Vietnamese based on the Asian Liver Center at Stanford University’s prior experiences in HBV knowledge surveys in HCWs [1315]. The questionnaire was pre-tested on seven volunteer HCWs to test the questions’ language, flow and comprehension.…”
Section: Methodsmentioning
confidence: 99%
“…In medical education, research has already indicated that the use of technologies and mixed learning methods, or syllabi with complementary activities online, enhance learning ( Boye et al, 2012 ; Heiman et al, 2012 ; Van Doorn and Van Doorn, 2014 ; Battat et al, 2016 ). Positive results using the online space for inter-professional education and collaborative cooperative learning were also observed by students ( Solomon et al, 2010 ; Shendell et al, 2016 ; Wang et al, 2016 ). Still, further research is needed to deep our understanding on the reasons to enroll, the skills needed to cope with this learning mode, and the challenges faced by learners.…”
Section: Discussionmentioning
confidence: 82%
“…transmission, prevalence, diagnostic testing, prevention, and treatment options), as well as, self-reported practice behavior. We have previously published extensively on our survey instrument [1522].…”
Section: Methodsmentioning
confidence: 99%